Economic evaluation of cell salvage in pediatric surgery. Issue 11 (17th August 2013) - Samnaliev, Mihail; Tran, Chau M.; Sloan, Steven R.; Gasior, Izabela; Lightdale, Jenifer R.; Brustowicz, Robert M.
Abstract: Background: Red blood cells are a scarce resource with demand outstripping supply. Use of intraoperative red cell salvage (CS) – the process of collecting shed blood during surgery and reinfusing it to patients – is often used as an effective blood conservation strategy. However, little is known about the economic impact of CS during pediatric surgery. Methods: A decision tree model was used to estimate the transfusion‐related costs per patient (2010 USD) from a healthcare system perspective of four transfusion strategies among children undergoing elective orthopedic or cardiac surgery: (i) CS followed by allogeneic transfusion, (ii) CS followed by autologous transfusion, (iii) allogeneic transfusion alone, and (iv) autologous transfusion alone. Results: Cell salvage and allogeneic transfusion was the least expensive strategy (USD 883.3) followed by CS and autologous blood transfusion (USD 1, 269.7), allogeneic transfusion alone (USD 1, 443.0), and autologous transfusion alone (USD 1, 824.7). Savings associated with CS use persisted in separate analyses of orthopedic and cardiac surgery, as well as in one‐way and probabilistic sensitivity analyses. Conclusions: Use of CS, particularly along with allogeneic blood transfusion, appears cost‐saving and cost‐effective in pediatric surgery.